Optimization of gallium oxide (ga2o3) nanomaterials for gas sensing applications - Gatsi, Nyepudzai Charsline (University of the Witwatersrand, Johannesburg, 2024)
Gas sensors are needed for monitoring different gases in indoor and outdoor environments, food quality assessment, and health diagnostics. Among materials studied for these applications, semiconducting metal oxides (SMOs) have generated a lot of interest due to their excellent sensitivity, simple circuit, and low cost. One-dimensional (1𝐷) 𝐺𝑎2𝑂3 nanomaterials are part of the promising candidates explored for the sensing of different gases due to their excellent electrical conductivity, high catalytic behavior, and chemical and thermal stability. This study reports the optimization of crystal structure, morphology, and surface chemistry of 𝐺𝑎2𝑂3 nanostructures for use in the detection of various gases. A set of unmodified and noble metal modified 1𝐷 𝐺𝑎2𝑂3 nanomaterials were synthesized by microwave-assisted hydrothermal method followed by heat-treatment at different temperatures and their gas sensing performances were systematically studied. The samples were characterized by thermogravimetric analysis (TGA), X-ray diffraction (XRD), Raman analysis, scanning electron microscope (SEM), transmission electron microscope (TEM), Brunauer-Emmett-Teller (BET), photoluminescence (PL), diffuse reflectance spectroscopy (DRS), and X-ray photoelectron spectroscopy (XPS) methods. The effects of heat-treatment temperatures on phase transformations and gas sensing performances of various 𝐺𝑎2𝑂3 polymorphs were investigated. The 𝛼 − 𝐺𝑎2𝑂3, 𝛽 − 𝐺𝑎2𝑂3 and 𝛼/𝛽 − 𝐺𝑎2𝑂3 crystal structures were synthesized and evaluated for gas sensing. The 𝛽 − 𝐺𝑎2𝑂3 sensing layers presented selective response coupled with fast response/recovery times towards carbon monoxide (𝐶𝑂) compared to the 𝛼 − 𝐺𝑎2𝑂3 and 𝛼/𝛽 − 𝐺𝑎2𝑂3 crystal structures. The observed variations in the gas sensing performances of these three crystal structures were attributed to controlled properties of different 𝐺𝑎2𝑂3 polymorphs. Furthermore, the 𝛽 − 𝐺𝑎2𝑂3 polymorph was prepared in the form of regular and hierarchical nanorod-based morphological features which demonstrated different gas sensing behaviors. The 𝛽 − 𝐺𝑎2𝑂3 regular nanorods showed better capabilities of detecting isopropanol than the nanobundle-like and nanodandelion-like features, and these differences were attributed to changes in textural, porosity, and compositional properties related to different morphologies. The effects of incorporating 𝐴𝑔 and 𝐴𝑢 noble metal nanocrystals on regular 𝛽 − 𝐺𝑎2𝑂3 nanorods surfaces on their gas sensing behaviour were also investigated. The results revealed that surface modification of 𝛽 − 𝐺𝑎2𝑂3 nanorods with 0.5 and 1.0 𝑚𝑜𝑙% 𝐴𝑔 and 𝐴𝑢 noble metals significantly lowered the sensor operating temperature compared to that of unmodified 𝛽 − 𝐺𝑎2𝑂3 nanorods towards the detection of ethylene. In addition, surface incorporation of 1.0 𝑚𝑜𝑙% 𝐴𝑔 dramatically increased the sensor sensitivity and selectivity and reduced the response/recovery times towards ethylene gas, and these positive changes were attributed to the electronic and chemical sensitization effects stimulated by the catalytic activity of 𝐴𝑔 nanocrystals incorporated on the surface of 𝛽 − 𝐺𝑎2𝑂3 nanorods. This study unambiguously optimized the crystal structure, morphology, and surface chemistry of 𝐺𝑎2𝑂3 nanostructures for the detection of carbon monoxide, ethylene and isopropanol gases. These sensors may potentially be used in real-time detection of carbon monoxide and isopropanol for indoor air quality monitoring to improve human health. In additional they have also demonstrated capabilities for the precise and economical detection of ethylene around plants and fruits, which could be beneficial to the horticultural and agricultural industries
A thesis submitted to the Faculty of Science in fulfillment of the requirements for the degree of Doctor of Philosophy in Physics , School of Physics University of the Witwatersrand, Johannesburg, 2024
Keywords: Gas sensing; Gallium oxide; Nanorods; Polymorphs; Microwave-assisted hydrothermal method; Nanostructures; Silver nanoparticles; Gold nanoparticles; UCTD; Photoluminescence; Defects; SDG-7: Affordable and clean energy